A Bifunctional Synthetic Peptide With Antimicrobial and Plant Elicitation Properties That Protect Tomato Plants From Bacterial and Fungal Infections - Montesinos, Laura; Gascón, Beatriz; Ruz, Lidia; Badosa, Esther; Planas, Marta; Feliu, Lidia; Montesinos, Emilio (Frontiers in Plant Science, 2021)
Abstract The hybrid peptide BP178 (KKLFKKILKYLAGPAGIGKFLHSAKKDEL-OH), derived from BP100 (KKLFKKILKYL) and magainin (1-10), and engineered for plant expression, had a strong bactericidal activity but not fungicidal. Moreover, the preventive spray of tomato plants with BP178 controlled infections by the plant pathogenic bacteria Pseudomonas syringae pv. tomato and Xanthomonas campestris pv. vesicatoria, as well as the fungus Botrytis cinerea. The treatment of tomato plants with BP178 induced the expression of several genes according to microarray and RT-qPCR analysis. Up-regulated genes coded for several pathogenesis-related proteins including PR1, PR2, PR3, PR4, PR5, PR6, PR7, PR9, PR10 and PR14, as well as transcription factors like ethylene transcription factors, WRKY, NAC and MYB, involved in the salicylic acid, jasmonic acid and ethylene-signaling pathways. BP178 induced a similar gene expression pattern to flg15 according to RT-qPCR analysis, whereas the parent peptide BP100 did not trigger such as a strong plant defense response. It was concluded that BP178 was a bifunctional peptide protecting the plant against pathogen infection through a dual mechanism of action consisting of antimicrobial activity against bacterial pathogens and plant defense elicitation on plant host.